Reflexão crítica na atividade reunião pedagógica - Gonçalves, Eduardo de Andrade (2007)
This work aims at investigating five pedagogical meetings in a language institution, in order to understand, based upon the ocial-historical-cultural perspective (Vygotsky, 1934/1993), their organization as an activity for analyzing, reflecting and discussing to co-construct actions for the classroom pedagogical problems. Inserted in Applied Linguistics field and based upon Activity Theory (AT) (Leont´ev, 1977/2003), upon Language Utterance Theory (Bakhtin, 1929/1995) and upon Critical Refection (Freire, 1970; Smyth, 1992; Schön, 1992, 2000; Kemmis, 1987), this research analyses the organization of this activity, emphasizing the role of the language as mediator of the relations carried out by the subjects considering the pedagogical meeting as the place for teacher s development. This study is a critical-action research of collaborative characteristic (Magalhães, 1998, 2002, 2004; Liberali, 1999, 2002, 2004) in which as participant, as pedagogical-coordinator and researcher, I intended to observe, analyze, understand and collaborate for the educational practices transformation of the institution in focus. The data were ategorized and analysed starting from the language action situations, thematic content, and rototypic sequences (Bronckart, 2003); the turn-taking to discuss the verbal interaction characteristics that took place during the process (Kerbrat-Orecchioni, 1992, 1998). The data analysis shows that the meetings didn t constitute themselves as places for collaborativecritical- reflection development, prevailing the pragmatic reflection and opinions based upon the common sense. In the same manner, the rules and labour division were established asymmetrically and the object construction was based upon the teacher s social needs and, therefore, apart from the aims idealized by the coordinator for the activity. It also suggests that the researcher-coordinator didn t make use of inquiries that could help the group with the development of new meanings established by the critical reflection process